The Effect of Taxpayer Awareness and Tax Service Quality on PBB Taxpayer Compliance - Indrawan, Rizki; Radite, Farhan Ali Wibowo (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2021)
This study aims to provide empirical evidence of taxpayer awareness and the quality of tax services on taxpayer compliance. The population of this study were all Land and Building Taxpayers in South Cimahi Regency who were registered at the Cimahi City BAPPEDA Office. The research sample is 150 taxpayers who are determined by using the Slovin formula and the data analysis method using the multiple linear regression analysis method. The results showed that partially taxpayer awareness has a positive and significant relationship with taxpayer compliance, while the quality of tax services does not have a significant relationship with taxpayer compliance. Simultaneously, taxpayer awareness and service quality have a positive and significant effect on taxpayer compliance.